Cardiac tumour in a patient with rheumatic heart disease. (30th June 2011) - Ananthakrishna, Rajiv; Nanjappa, Manjunath C; Kamalapurkar, Giridhar; Bhat, Prabhavathi; Panneerselvam, Arunkumar; Chander, Naveen; Chandrasekaran, Dhanalakshmi
Abstract : A 45-year-old female known to suffer from rheumatic heart disease (RHD), presented with breathlessness of 1 year duration. Two-dimensional echocardiography revealed significant mitral and aortic valve disease mandating double valve replacement. In addition, an unusual finding in the form of a well-defined, densely calcified intramyocardial left ventricular mass was noted on echocardiography. The nature and extent of the mass was assessed by additional imaging modalities. Patient underwent excision of the mass followed by double valve replacement. Histopathology was consistent with cardiac calcific amorphous tumour (CAT). An unusual occurrence of CAT in a patient with RHD is presented herein. This rare tumour has not been previously described in patients with RHD.